(untitled) (Revista Argentina de Cirugía, 2026)
Ectopic cervical thymoma is a rare entity; therefore, its diagnosis is often difficult. It should be considered as a differential diagnosis in patients with lateral cervical masses, especially those close to the thyroid gland. Surgical treatment is indicated with complete excision of the lesion. Cervical thymomas are slow-growing tumors, usually benign. In this case report, due to tumor size and location, it was necessary to separate it from the large vessels and adjacent nerve structures, resulting in a more complex procedure.